2020
DOI: 10.1080/14767058.2020.1793318
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 is not present in the vaginal fluid of pregnant women with COVID-19

Abstract: Background: Data concerning the presence of SARS-CoV-2 in the female genital system is scarce; however, this information is important for understanding whether the virus can transmit sexually or from mother to child. The aim of this study was to investigate whether pregnant women with COVID-19 have virus in their lower genital tract. Methods: In this cross-sectional study, we present an analysis of prospectively gathered data collected at a single tertiary university hospital from 19 April to 19 May 2020. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 9 publications
3
41
1
2
Order By: Relevance
“…Three studies examined female genital tract secretions for the presence of SARS-CoV-2, showing consistent results [73][74][75]. Aslan et al [73] included 12 pregnant women with confirmed COVID-19 and moderate symptoms. Vaginal swabs were obtained during the hospitalization period.…”
Section: Sexual Transmission In Womenmentioning
confidence: 92%
See 1 more Smart Citation
“…Three studies examined female genital tract secretions for the presence of SARS-CoV-2, showing consistent results [73][74][75]. Aslan et al [73] included 12 pregnant women with confirmed COVID-19 and moderate symptoms. Vaginal swabs were obtained during the hospitalization period.…”
Section: Sexual Transmission In Womenmentioning
confidence: 92%
“…Vaginal swabs were obtained during the hospitalization period. All lower genital tract samples were negative for SARS-CoV-2 [73]. Qiu et al analyzed vaginal samples of 10 women with severe COVID-19 pneumonia admitted to an ICU.…”
Section: Sexual Transmission In Womenmentioning
confidence: 99%
“…5 However, our findings contradict previous reports, which did not detect the presence of viral colonization in the vagina. [9][10][11] This discrepancy can be explained by the small number of cases in each group. Since we assume that vaginal colonization of SARS-CoV-2 has relatively low incidence, larger studies are required to confirm our findings.…”
Section: Main Findingsmentioning
confidence: 96%
“…Hysteroscopy has the theoretical risks of viral dissemination when performed in COVID- 19 Recent studies have confirmed the presence of viral particles in urine, feces, blood, and tears in addition to the respiratory tract in patients infected with COVID-19. 3,14,15 The presence of the SARS-CoV-2 virus in the female genital system is currently unknown. Previous studies, of other epidemic viral infections, have demonstrated the presence of the virus in the female genital tract in affected patients of Zika virus and Ebola.…”
Section: Is There Risk Of Viral Dissemination During Hysteroscopic Prmentioning
confidence: 99%
“…Previous studies, of other epidemic viral infections, have demonstrated the presence of the virus in the female genital tract in affected patients of Zika virus and Ebola. 16,17 However, 2 recent studies have failed to demonstrate the presence of the SARS-CoV-2 virus in the vaginal fluid of pregnant 14 and not pregnant 18 women with severe COVID-19 infection.…”
Section: Is There Risk Of Viral Dissemination During Hysteroscopic Prmentioning
confidence: 99%